Women and food security in South Asia: Current issues and emerging concerns - Nira Ramachandran (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2006)
The food security scenario in South Asia has witnessed rapid progress over the last few decades, yet nutrition outcomes, especially those related to women and children, have failed to keep pace. This paper contends that the role of women in providing food and nutrition security at the household and individual level needs to be examined, if the paradox of persisting malnutrition amid macro level food sufficiency is to be resolved. Food security, in its broader connotation, results from the availability of adequate food, effective consumption, and desirable nutrition outcomes. As such, it is intricately linked with a woman's multiple roles expressed in her productive, reproductive, and caring functions. However, even focussed efforts aimed at resolving the problems faced by women in performing one or other of their roles, may fail to produce expected results, if the issues underlying each function and their inter-linkages are not fully understood. The paper thus attempts to review various aspects of the relationship between women and food security in South Asia, highlight the issues that require urgent focus and indicate emerging concerns in the region.
Keywords: Q15; Q18; J16; J43; 330; food security; gender bias; gender food security; women farmers; female workforce; feminization of poverty; wage differentials; malnutrition; empowerment; Nahrungsmittelversorgung; Geschlecht; Frauenerwerbstätigkeit; Frauen; Südasien